Liquidity risk: An Islamic banking perspective / Nur Hazimah Amran and Wahida Ahmad - Amran, Nur Hazimah; Ahmad, Wahida (Universiti Teknologi MARA, Perlis, 2017)
The purpose of this study is to investigate the factors influencing the liquidity risk based on the ASEAN Islamic banking perspectives. The latent independent variable in this study is the liquidity ratio, meanwhile, the independent variables are; (i), profitability, (ii) capital adequacy, and (iii) bank capitalization. It is a unique study as the Islamic banking is another type of banking system which is rapidly growing in many countries. Regardless of numbers of Muslim population, Islamic banks currently exist in both Islamic and non-Islamic countries. This study hence would benefit those who are practicing in the finance and banking sectors. This study use a ten (10) years unbalanced panel data dated from the year 2005 to 2014. The sample consists of thirty (30) Islamic banks from six ASEAN countries. By using random effects model, the regression results reveal that profitability and bank capitalization have a negative relationship while profitability has a positive relationship to ASEAN Islamic banks liquidity risk. All independent variables are found to be significant to the liquidity risk except for the profitability which is statistically insignificant. On the other hand, both capital adequacy and bank capitalization are statistically significant at 1% significant level